2012
DOI: 10.5402/2012/592648
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Fetal Antigen 1 in Extreme Nutritional States

Abstract: Objective. Recent data suggest that fetal antigen (FA1) is linked to disorders of body weight. Thus, we measured FA1 serum levels in two extreme nutritional states of morbid obesity (MO) and anorexia nervosa (AN) and monitored its response to weight changes. Design. FA1 and insulin serum concentrations were assessed in a cross-sectional study design at defined time points after gastric restrictive surgery for 25 MO patients and 15 women with AN. Results. Absolute FA1 serum levels were within the assay normal r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Furthermore, increasing expression of Dlk1 has been shown to be associated with insulin resistance in diabetic Goto-Kakizaki rat (20) and mice (21). Additionally, human studies have demonstrated changes in serum levels of FA1 in an extreme nutritional state (22) and during weight loss following bariatric surgery (23).…”
mentioning
confidence: 99%
“…Furthermore, increasing expression of Dlk1 has been shown to be associated with insulin resistance in diabetic Goto-Kakizaki rat (20) and mice (21). Additionally, human studies have demonstrated changes in serum levels of FA1 in an extreme nutritional state (22) and during weight loss following bariatric surgery (23).…”
mentioning
confidence: 99%